Analysis Of The Effect Of Competence And Objectiveness On The Quality Of Internal Audit Results In The Inspectorate Of Medan City - IRNA TRIANNUR LUBIS (Institute of Computer Science (IOCS), 2021)
The phenomenon that occurs in this study is that the results of internal audit quality have an effect on the opinions issued by external auditors, if the results of the internal audit quality produced by the Medan City Inspectorate are good, the opinions generated by the external auditor (BPK) will be good and vice versa. Based on the report on the results of the BPK examination above, it shows that for four consecutive years the Medan city government has always received a Fair with Exception (WDP) opinion on the Financial Statements. Good audit quality is determined by an auditor's compliance with applicable standards, standards and guidelines on audit ethics greatly assist auditors in establishing principles on how to overcome ethical temptations. The purpose of this study was to determine the effect of competence and objectivity on the quality of audit results. The data analysis technique used is the Partial Least Square (PLS) approach. Where PLS is a model of Structural Equation Modeling (SEM) equations based on variables or components. The results showed that competence and objectivity had a significant effect on the quality of internal audit results at the Medan city inspectorate.